Diverse Construction of Identities in Contemporary Malaysian Literature: Challenges in Deconstructing and Teaching Literature - Collin, Jerome; Ting, Su Hie (2015)
Contemporary Malaysian literature functions as a site of diverse constructions of identity where local writers construct various identities of their fictional characters and their own identities in the process. Their dilemma in writing about these identities in their works, that is, aligning themselves to certain social identities such as ethnicity, religion, and regional origin or embracing various identities to call themselves “Malaysian” is coming to the fore but not gaining enough recognition because previously literary texts have tended to portray single identity/ies. This paper addresses the diverse constructions of identity in contemporary Malaysian literature using one literary text, Neighbours. Using theories relating to identity formation, the analysis, among others, indicated that the identity of the protagonist that is foregrounded is Malay identity but diverse identities that are backgrounded include gender, sexual and ethno-religious identities. However, these diverse identities still exert influence on the realization of the dominant social identity, highlighted in incidents and issues discussed by the characters in the fictional work. The challenges in deconstructing, and therefore teaching these diverse identities in literature in the plural Malaysian nation-state, are discussed.